Changes in extreme climate events in eastern China during 1960–2013: A case study of the Huaihe River Basin. (4th September 2015) - Zhang, Wei; Pan, Shaoming; Cao, Liguo; Cai, Xun; Zhang, Kexin; Xu, Yihong; Xu, Wei
Abstract: Within the context of global warming, climate extremes, including extreme wet event and drought events, have become one of the most significant and attractive themes around the world. The target region of this study is confined to eastern China, with most of the country's population concentrated, where both the wet and drought climate extremes can cause considerable damages to the economy, particularly to agriculture. From the inter-annual and intraseasonal scale, temporal and spatial distributions of climate extremes for 27 stations in the Huaihe River Basin over the period 1960–2013, are examined rigorously by means of a modified FAO Penman-Monteith method and the standardized variables of the monthly Surface Humid Index. Morlet wavelet analysis is utilized to thoroughly investigate the oscillation and periodicity of extreme wet/drought events during four seasons, as well as the whole year. The results suggest that the frequency of extreme wet events has significantly increased by 0.0118 times/year, whereas the trend for extreme drought events has gradually decreased, at the rate of 0.0127 times/year, both of which are in accordance with inter-decadal variations of climate extremes. Comparative study reveals climate extremes in autumn shows great differences, in sharp contrast to other seasons and the general inter-annual tendency. Spatial distributions of inter-annual extreme climate events exhibit certain symmetry characteristics, from west to east, indicating the combined influences of topography and monsoon circulation. The major cycles of extreme wet and drought events are 14 years and 24 years, respectively. Finally, possible causes of the temporal and spatial distributions of climate extremes are tentatively analyzed, by correlation analysis of six indexes, namely, AOI, AAOI, EASMI, WNPMI, SASMI, and NAOI, with AOI and NAOI being the dominant indexes under the background of large-scale atmospheric circulation. Additionally, other factors such as total annual precipitation, northward movement and enhancement of the subtropical anticyclone, and anthropogenically induced greenhouse forcing can also contribute to the changes in extreme climate events.